2018
DOI: 10.1002/uog.18936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fetal hemodynamics on growth in fetuses with single ventricle or transposition of the great arteries

Abstract: We found no associations of CCO or MCA- and UA-PI with late gestational weight gain or biometry at birth in fetuses with CHD. This does not support fetal hemodynamics as the primary driver of suboptimal fetal growth in fetuses with SV. Future research could further explain genetic and placental abnormalities that may affect fetal growth in those with CHD. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 33 publications
2
30
2
Order By: Relevance
“…With progressive hypoxia as in cases of FGR, blood flow increases to compensate for the decrease in available oxygen (brain-sparing effect). 33,35 Our previous study showed no association of the MCA-PI with head circumference in any group. 34 Previous work showed reduced MCA-PI in HLHS suggesting a vasodilatory response in the cerebral vasculature as there is retrograde flow through the transverse arch and higher MCA-PI in non-HLHS SV suggests a higher cerebral vascular resistance.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…With progressive hypoxia as in cases of FGR, blood flow increases to compensate for the decrease in available oxygen (brain-sparing effect). 33,35 Our previous study showed no association of the MCA-PI with head circumference in any group. 34 Previous work showed reduced MCA-PI in HLHS suggesting a vasodilatory response in the cerebral vasculature as there is retrograde flow through the transverse arch and higher MCA-PI in non-HLHS SV suggests a higher cerebral vascular resistance.…”
Section: Discussionmentioning
confidence: 69%
“…34 Previous work showed reduced MCA-PI in HLHS suggesting a vasodilatory response in the cerebral vasculature as there is retrograde flow through the transverse arch and higher MCA-PI in non-HLHS SV suggests a higher cerebral vascular resistance. 33 Most of the fetuses in the non-HLHS SV group have right ventricular outflow tract obstruction and the majority of the CCO flows through the ascending aorta. The elevated resistance suggests a regulatory mechanism to control cerebral blood flow in this population.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations